Chlorite-Hemoprotein Interaction as Key Role for the Pharmacological Activity of the Chlorite-based Drug WF10 - Schempp, Harald; Reim, Manfred; Dornisch, Kerstin; Elstner, Erich F. (Arzneimittelforschung, 2001)
WF10 is a chlorite-based drug that modulates macrophages functional states and can be safely administered to humans. WF10 potentially modulates disease-related up-regulation of immune responses both in vitro and in vivo. Thus immune response is influenced in a way that inappropriate inflammatory reactions are downregulated. The molecular mechanisms involved are not completely understood. Biochemical data suggest the reaction of chlorite with hemoproteins as the central step in the activation process of the drug. Thereby a chlorinating agent is generated, resulting in the oxidation of reduced sulfur-containing molecules and in the conversion of amino residues into more or less stable chloramines. The most prominent chloramine in vivo is taurine chloramine. Taurine chloramine is a long-lived molecule with immunomodulatory properties. For instance, taurine chloramine inhibits the generation of macrophage inflammatory mediators such as nitric oxide, prostaglandin E2 (PGE2), tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). This study on the biochemical mechanism of WF10 gives evidence that hemoprotein dependent chlorination of taurine is not only observed in vitro but also very likely in vivo. To characterize the oxidant, generated during heme activation, different methods were used: Chemiluminescence, EPR-spectroscopy, UV/VIS-spectroscopy, gas (GC) and size exclusion chromatography. In summary, the results indicate as the first products of hemoprotein catalyzed chlorite activation a chloroxygenspecies (probably HOCl/OCl−) and a ferryl-oxygen species at the hemoprotein active site in analogy to the known peroxidase (compound I and II) intermediates. Moreover, hydrogen peroxide and chlorite seem to react in a similar way with heme centers. It is proposed that WF10 represents an “inactive” transport form of potentially active chlorine. Reactivity of the latter is restricted unless heme moieties in proteins or enzymes activate the “transport form” to perform reactions in analogy to peroxidases (i.e. myeloperoxidase-catalyzed formation of HOCl/OCl−).
Keywords: Chlorite; Hemoglobin; Hemoproteins; Immunomodulation; Macrophages; WF 10, chlorite-hemoprotein interaction, immunomodula-tion, pharmacology